2021
DOI: 10.1016/j.jneumeth.2020.108990
|View full text |Cite
|
Sign up to set email alerts
|

Towards in vivo g-ratio mapping using MRI: Unifying myelin and diffusion imaging

Abstract: Highlights Second review on the topic of g-ratio mapping using MRI. A summary of the most recent developments in the fieldproviding methodological background. Discussion of pitfalls associated with g-ratio mapping using MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 151 publications
(380 reference statements)
2
75
0
Order By: Relevance
“…A common metric to quantify the degree of myelination is the g -ratio, which is defined as the inner over the outer radii of the myelin sheath 2 . Using multiple MRI modalities one can obtain an estimate of the average voxel-wise g -ratio in a voxel in- vivo by combining measurements of myelin and axonal volume fractions 10-13 . The axonal volume fraction can be estimated from diffusion MRI, using a multi-compartment fit to the diffusion-weighted signal 14-18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common metric to quantify the degree of myelination is the g -ratio, which is defined as the inner over the outer radii of the myelin sheath 2 . Using multiple MRI modalities one can obtain an estimate of the average voxel-wise g -ratio in a voxel in- vivo by combining measurements of myelin and axonal volume fractions 10-13 . The axonal volume fraction can be estimated from diffusion MRI, using a multi-compartment fit to the diffusion-weighted signal 14-18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also an average across fibre populations in voxels where multiple fibres cross each other, which is a common configuration in the human brain 29,30 . Furthermore, this approach relies on the accuracy of the volume fraction estimates 31 , which has been questioned for both the axonal volume fractions 32 and the myelin volume fractions 13,19,20 . Here we aim to overcome these limitations by proposing a novel sequence, which is directly sensitive to the g -ratio (rather than the volume fractions) and allows to distinguish between crossing fibres.…”
Section: Introductionmentioning
confidence: 99%
“…axon) and outer (i.e. axon and myelin) diameter of the WM fibre and reflects myelin thickness relative to the axon radius [5254]. Preliminary studies in small subject groups have observed g-ratio abnormalities in MS, suggestive of a thinner myelin sheath, in accordance with known pathological changes in this disease [53,55,56].…”
Section: Introductionmentioning
confidence: 95%
“…The MT saturation map was obtained from the hMRI toolbox as described above. For calibration of the MT saturation map to a myelin-volume fraction map (MVF MR = α MT sat ), we used the g-ratio based calibration method as reported in Ellerbrock and Mohammadi (2018) and Mohammadi and Callaghan (2020), with a reference g-ratio value of 0.7 in the splenium (Mohammadi et al, 2015a), yielding α = 0.217.…”
Section: Application To G-ratio Mappingmentioning
confidence: 99%
“…The beneficial effect of using the consecutive HySCO WA combined diffusion data was illustrated for g-ratio mapping, where blurring effects can reduce the overlap between the diffusion-MRI-based axonal biomarker and the myelin marker maps. The blurring artefacts in diffusion MRI (which are decreased when using a WA combination) lead to a worse delimitation between grey and white matter, which in turn can propagate towards the resulting g-ratio map (Mohammadi and Callaghan, 2020). As the MR g-ratio is defined only in white matter (Stikov et al, 2015), it is typically created by combining an axonal water fraction estimated in the white matter probability maps from diffusion MRI (here, the AWF) and a white matter myelin biomarker map (here, the MT saturation).…”
Section: Application To G-ratio Mappingmentioning
confidence: 99%